The Response of Dayah Residents to Hydrometeorological Disasters: An Exploratory Study from the Perspective of Islamic Ecotheology in Pidie Jaya Regency Aceh Province - Ash Shifa Annur; Salami Mahmud; Zulfatmi; Muji Mulia (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
hydrometeorological disasters, including floods, flash floods, strong winds, and extreme rainfall. Within the socio-religious context of Acehnese society, dayah (Islamic boarding schools) play a strategic role not only as centers of Islamic education but also as institutions that foster social values, spiritual resilience, and environmental awareness. This study aims to examine the responses of dayah communities to hydrometeorological disasters and to analyze the role of dayah in disaster management from the perspective of Islamic ecotheology. A qualitative approach with an exploratory case study design was employed in three dayahs located in Meurah Dua District, Pidie Jaya Regency. Data were collected through in-depth interviews, field observations, and document analysis and were analyzed using thematic analysis. The findings reveal that dayah communities respond to disasters through pre-disaster preparedness, emergency response, and post-disaster recovery activities grounded in spiritual values, social solidarity, and local wisdom. Islamic ecotheological principles, particularly khalifah (stewardship), amanah (trust), and mizan (balance), serve as the foundation for environmental awareness, disaster preparedness, and community resilience. Dayahs also function as centers for disaster education, psychosocial support, humanitarian assistance, and the dissemination of environmental conservation values. However, limited mitigation infrastructure, inadequate technical disaster management capacity, and weak coordination with external institutions remain significant challenges. The study concludes that integrating Islamic ecotheology, local wisdom, and modern disaster science can strengthen community-based resilience and contribute to sustainable hydrometeorological disaster management.